The Influence of Entrepreneurial Activities on Adoption of Tissue Culture Banana Seedlings in Tanzania. - Tumaini, Steven; Raphael, Ghahula; Salvio, Macha (IJBLE Scientific Publications Community Inc., 2024)
Banana is the world’s most popular fruit, with an estimated global export value of 7 billion dollars per year; they are also one of the most domestic foods and are traded by Tanzania farmers. However, approximately 15% of the global banana production is involved in trade. The inadequate adoption of Tissue Banana Seedlings has led to the assessment of the Influence of Entrepreneurial Activities on the Adoption of Tissue Culture Banana Seedlings in Tanzania-Kilimanjaro particularly. The study adopted a positivism philosophy, a cross-sectional survey design, and purposive sampling techniques targeting 350 farmers. Questionnaires were used for data collection, Binary Logistic Regression was applied for data analysis, the results show Entrepreneurial significantly influenced the adoption of Tissue culture seedlings, and Tissue culture seedlings offer more business opportunities than local suckers. Therefore, the study recommends promoting Entrepreneurial activities toward the adoption of tissue culture banana seedlings in Tanzania and developing countries